2007
DOI: 10.1007/s00128-007-9151-5
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Quality Status of Two Creeks in the Upper Bonny Estuary, Niger Delta, in Relation to Urban/Industrial Activities

Abstract: Two creeks (Azuabie and Obufe) in the upper Bonny Estuary, Nigeria were studied to determine how industrial and other anthropogenic activities have influenced their relative sediment qualities. Total organic carbon, total hydrocarbons, zinc, lead, cadmium and iron were significantly higher in the Azuabie creek, while phosphate, nitrate, copper and chromium did not show significant differences between the two creeks. Principal component analysis (PCA) ordinations discriminated all locations in the Obufe creek i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
2
10
1
Order By: Relevance
“…Station 2 had the highest pH value in the month of May, station 4 in the month of June and station 4 also in the month of July. The values obtained for sediment pH levels during this study were consistent with those of Daka et al [16] who recorded range between of 2.5 -3.5 in Azuabie creek of the upper Bonny Estuary. These values are acidic and would pose serious challenges to organisms in nature.…”
Section: Discussionsupporting
confidence: 92%
“…Station 2 had the highest pH value in the month of May, station 4 in the month of June and station 4 also in the month of July. The values obtained for sediment pH levels during this study were consistent with those of Daka et al [16] who recorded range between of 2.5 -3.5 in Azuabie creek of the upper Bonny Estuary. These values are acidic and would pose serious challenges to organisms in nature.…”
Section: Discussionsupporting
confidence: 92%
“…The concentration of heavy metals observed in this study is comparable to the range reported in fish (mudskipper) muscle tissues [5] but generally higher compared to values recorded in different fish species from the study area [31]. The implication of this is gradual accumulation of heavy metal in biota of the Azuabie creek which is attributable to anthropogenic activities in the study area including the discharge of domestic, industrial and municipal wastes into the creek [32,33,34,35,5]. The levels of Pb, Cd and Ni observed in this study also exceeded the recommended maximum permissible limits [28] and [36].…”
Section: Discussionsupporting
confidence: 78%
“…The recognition of this connection and the need to protect human health, recreation and fisheries production led to the early development of water quality regulations and monitoring methods [1,2]. Contaminats of aquatic ecosystems can be confirmed by determining levels of contaminants in water, sediment and organisms [3,4]. Industrial effluents, agricultural run-offs, transport, burning of fossil fuels, animal and human excretions, geologic weathering and domestic waste contribute to the metal levels in water bodies [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%